Paciente de sexo femenino de 26 años diagnosticada con aniseiconía y derivada a cirugía refractiva. - Saltos Jiménez, María Belén (2021)
The present clinical case deals with a 26-year-old female patient diagnosed with aniseiconia and referred to refractive surgery. Aniseiconia is a binocular disorder where there is a difference in the sizes and shapes of the ocular images visualized by the eyes, characterized by headache, difficulty reading, dizziness, eye fatigue, vertigo, double vision, sensitivity to light, nausea, distortion of spatial vision and bodily discomfort. The objective of the study is to establish the effects of aniseiconia in a 26-year-old female patient. The applied methodology is based on the analysis of the clinical history, pathological, family and surgical antecedents; In addition to physical examinations (objective and subjective visual acuity, fundus, biomicroscopy, retinoscopy, ocular motility) and complementary examinations (Aniseikonia Test), which served to make a definitive diagnosis that resulted in aniseiconia with the presence of high myopia of a grade of 5.8% and prescribe the appropriate treatment according to the needs of the patient. The results were obtained that: the patient presents headache, vertigo, sensitivity, difficulty reading, eye fatigue, distortion of spatial vision and burning; The established treatment to treat the condition is based on corrective, pharmacological and non-pharmacological treatment.